A systematic review on evaluating school safety signs and ways to improve its effectiveness - Wang, Tongxu; Abdul Shukor, Shureen Faris; Kozlowski, Marek; Wan Mohamed, Wan Srihani; Zhang, Ting (Frontiers in Communication, 2025)
IntroductionSafety signs are essential visual communication tools that convey critical information regarding hazards, regulations, and emergency procedures across various environments. Their significance has garnered considerable attention due to their role in enhancing public safety. However, existing studies have predominantly focused on design factors, with limited research addressing the interaction of non-design factors among specific age groups and safety communication in public spaces, particularly concerning young children’s cognitive abilities and perceptions.MethodsThis systematic review aims to comprehensively analyze the characteristics and effectiveness of safety signs within the school environment. A systematic review of the literature on safety signs—specifically their design within school premises—was conducted using the Systematic Review and Meta-Analyses (PRISMA) approach to identify research gaps. Query strings were utilized to extract papers, identifying 48 peer-reviewed articles from 2000 to 2024 for review.ResultsThe review found that visual elements, such as dynamic safety signs and the use of highly saturated colors, significantly enhance the effectiveness of warnings. Several factors were identified that influence the efficacy of safety signs, including age-related cognitive abilities and the contextual understanding of young children. Additionally, the study highlights the effectiveness of technological tools, such as eye tracking and virtual reality (VR), for assessing human perception and improving testing methodologies. The role of enjoyment and experiential learning in enhancing safety communication are beneficial.DiscussionThis systematic review underscores the importance of considering both design and non-design factors in safety sign development, particularly in school environments. The findings suggest that dynamic, visually appealing signs, along with the use of advanced technological tools, can improve the effectiveness of safety messages. The integration of experiential learning also contributes to a better understanding of safety information. This review is a valuable resource for safety science researchers, visual designers, and policymakers by providing insights into the current state of research, identifying research gaps, and offering perspectives on the future of school safety signage pertinent to school-age children.